Characterization of specific p63 and p63-N-terminal isoform antibodies and their application for immunohistochemistry - Nekulova, Marta; Holcakova, Jitka; Nenutil, Rudolf; Stratmann, Rembert; Bouchalova, Pavla; Müller, Petr; Mouková, Lucie; Coates, Philip J; Vojtesek, Borivoj (Virchows Archiv, 2013)
The TP63 gene gives rise to protein isoforms with different properties and functions due to the presence (TAp63) or absence (ΔNp63) of an N-terminal p53-like transactivation domain. Immunohistochemistry for p63 has clinical value for certain tumour types, but investigations have been hampered by a lack of well characterized antibodies and the inability to discriminate between these N-terminal isoforms with opposite functional properties. We have extensively characterized a series of monoclonal antibodies to recombinant human TAp63 and two commercial p63 monoclonals by Western blot, immunostaining and phage display epitope mapping. Twenty-eight of 29 (96.6 %) novel monoclonals that recognized all p63 isoforms showed substantial cross-reactivity with p73, as did the commercial antibody, 4A4. One novel clone, PANp63-6.1, showed slight cross-reaction with p73 by Western blotting but not immunohistochemistry and the SFI-6 monoclonal did not cross-react with p73 or p53. Phage display revealed that the PANp63-6.1 epitope has one amino acid difference between p63 and p73, the 4A4 epitope is identical in both, whereas the SFI-6 epitope is unique to p63, accounting for these findings. We also produced and characterized a TAp63-specific clone that does not recognize p53 or p73, and we prepared polyclonal sera specific for ΔNp63 isoforms. Immunohistochemistry demonstrated that TAp63 is expressed in a variety of epithelial and other cell types during development, often in a converse pattern to ΔNp63, but has a very limited expression in normal adult tissues and is independent of ΔNp63. TAp63 was expressed in 17.6 % of squamous cancers of cervix that expressed p63, unlike normal cervix where TAp63 was not expressed. TAp63 did not associate with proliferative index, but cervical carcinomas with TAp63 expression showed improved survival. These data highlight the need for rigorous antibody characterization and indicate that p63-isoform identification may improve the clinical value of p63 expression analyses.
Keywords: Cross Reactions; Protein Isoforms; monoklonální protilátky; zkřížené reakce; nádory plic; Carcinoma, Non-Small-Cell Lung; protein p73; Cell Line, Tumor; Lung Neoplasms; Uterine Cervical Neoplasms; nádory děložního čípku; membránové proteiny; Tumor Suppressor Proteins; Membrane Proteins; jaderné proteiny; imunohistochemie; nádory prsu; DNA vazebné proteiny; nádorový supresorový protein p53; protein - isoformy; nádorové supresorové proteiny; krysa rodu Rattus; kultivované buňky; Animals; Antibody Specificity; lidé; specificita protilátek; ženské pohlaví; Immunohistochemistry; adenokarcinom; Breast Neoplasms; nemalobuněčný karcinom plic; zvířata; Humans; Rats; Tumor Protein p73; myši; Cells, Cultured; Antibodies, Monoclonal; nádorové buněčné linie; spinocelulární karcinom; Adenocarcinoma; Female; Mice; Nuclear Proteins; DNA-Binding Proteins; Tumor Suppressor Protein p53; Carcinoma, Squamous Cell